Peran Guru PPKn Terhadap Implementasi Nilai-Nilai Pancasila Melalui Cooperative Learning di Kelas VIII D SMPN 17 Kota Malang - Engelbertus Kukuh Widijatmoko; Suparno Suparno; Nurlaila Syamsudin (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This research uses a qualitative approach to identify societal issues that affect both individuals and communities. At SMP Negeri 17 Malang City, the principal, student representatives, PPKn teachers, and a number of students served as data sources. Data collection methods included observation, interviews, and documentation. The collected data includes both primary and secondary sources. We used both formal and unstructured interviewing methods. This study's data analysis process included three steps: data reduction, data presentation, and conclusion/verification. We also used triangulation methods to assess the validity of the data. Pre-field, fieldwork, involvement during data collection, and data analysis are the phases of the study process. To define Pancasila ideals and learn how to apply them using the cooperative learning model at SMP Negeri 17 Malang City, this research set out to ascertain the role that PPKn instructors play in doing so. The study's findings demonstrated that instructors have a responsibility to care for, acknowledge, and counsel pupils who lack motivation or discipline in addition to imparting knowledge. To prevent such issues, it is recommended that future research focus more on the role PPKn instructors play in boosting students' enthusiasm to study and selecting learning models that fit the infrastructure and facility requirements.